Who else has the magic wand? An evaluation of a residential unit for younger children - Susan Elsley (Scottish Journal of Residential Child Care)
Residential care for younger children raises complex issues. Should younger children be placed in residential care? If they are, how does a service respond to their needs? What evidence is available about the experience of younger children in residential care? Do they require additional or different care in comparison with older children and young people? These questions are all relevant to the study of residential services for younger children, an area which is little researched in Scotland and across the UK. This paper aims to contribute to the existing research by considering some of the findings from an evaluation of a residential service (The Unit) for younger children run by Aberlour Child Care Trust.